2016
DOI: 10.1007/s40726-016-0031-7
|View full text |Cite|
|
Sign up to set email alerts
|

Lightning NO x and Impacts on Air Quality

Abstract: Lightning generates relatively large but uncertain quantities of nitrogen oxides (NO x ), critical precursors for ozone and hydroxyl radical (OH), the primary tropospheric oxidants. Lightning NO x strongly influences background ozone and OH due to high ozone production efficiencies in the free troposphere, effecting small but non-negligible contributions to surface pollutant concentrations. Lightning globally contributes 3-4 ppbv of simulated annual-mean policy-relevant background (PRB) surface ozone, comprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(144 citation statements)
references
References 192 publications
(253 reference statements)
2
122
0
3
Order By: Relevance
“…This might be connected to advection of tropospheric ozone and precursors from intense lightning regions of Africa (in the lower and middle troposphere) and South America (in the upper troposhere) (Finney et al, 2016;Grewe, 2007;Murray, 2016). All the parameterizations show nonnegligible O 3 increase at ∼10 • S over the Atlantic Ocean where lightning density and NO enhancement are small (with respect to the maxima in central Africa).…”
Section: Annual Global Averaged Chemical Distributionmentioning
confidence: 90%
“…This might be connected to advection of tropospheric ozone and precursors from intense lightning regions of Africa (in the lower and middle troposphere) and South America (in the upper troposhere) (Finney et al, 2016;Grewe, 2007;Murray, 2016). All the parameterizations show nonnegligible O 3 increase at ∼10 • S over the Atlantic Ocean where lightning density and NO enhancement are small (with respect to the maxima in central Africa).…”
Section: Annual Global Averaged Chemical Distributionmentioning
confidence: 90%
“…Within the GMI CTM, lightning is calculated with a two‐step procedure involving (1) a determination of lightning flash frequency and lightning NO x production rate for each model grid cell and (2) the repartitioning of lightning NO x emissions in the vertical column (Allen et al, ). However, it has been shown that the impact of lightning on surface‐level O 3 is small in the contiguous United States (Murray, ).…”
Section: Methodsmentioning
confidence: 99%
“…Biogenic VOC emissions follow the Model of Emissions of Gases and Aerosols from Nature scheme version 2.1 (Guenther et al, 2012). Lightning NO x emissions are as described by Murray (2016). Soil microbial NO x emissions are described by Hudman et al (2012).…”
Section: Geos-chemmentioning
confidence: 99%